The Legal Position of Insurance Agreement (Borgtocht) as a Form of Credit Bindings - Wahyu Adi Wibowo; Siti Rodhiyah Dwi Istinah; Ira Alia Maerani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to examine and analyze the credit agreement at PT BPR Surya Yudhakencana Banjarnegara Purwokerto Branch and to examine and analyze the legal position of the guarantee agreement (Borgtocht) as a form of credit binding at PT BPR Surya Yudhakencana Banjarnegara Purwokerto branch and to determine the form of the guarantee agreement deed (Borgtocht). ).The research approach method is a sociological juridical research method. The research specification uses descriptive analysis. The types and sources of research data are divided into two, namely primary data and secondary data. Methods of data collection by using the interview method, study documents or library materials. The data analysis method uses qualitative analysis, namely by using the data that has been obtained to then connect it with the provisions and legal principles related to the problem under study with an inductive logic, namely thinking from the specific to the general. The results showed that PT BPR Surya Yudhakencana Banjarnegara Purwokerto Branch did not yet have an SOP in the implementation of the guarantee agreement (Borgtocht), however, in its implementation, it is still guided by the standard rules that apply to civil law in the provisions of Article 1313 of the Civil Code and Article 1320 of the Civil Code. The existence of the 6C indicator in the selection of borg, so that the position of the insurer (Borgtocht) has the power to carry out the function as guarantor according to the underwriting agreement deed that has been agreed and signed.